Answer:
-26
Step-by-step explanation:
well add the negative numbers first so you get
-17-18=(-35)
then you add 9 so its (-35)+9=26
4 - (0) = y
4 - 0 = 4 y = 4
4 - (1) = y
4 - 1 = 3 y = 3
4 - (2) = y
4 - 2 = 2 y = 2
4 - (3) = y
4 - 3 = 1 y = 1
Answer:
6
Step-by-step explanation:
The expression can be rearranged to ...
b = 3 -9/(a+5)
In order for b to be an integer, (a+5) must be an integer divisor of 9. There are exactly 6 of those: ±1, ±3, ±9.
The attached table shows the values (a, b) = (x₁, f(x₁)).
Answer:a)680cu.ft
b)180cu.ft
Hope this helped you...
Step-by-step explanation:
Answer:
C
Step-by-step explanation:
Both of the y= make upward parabolas
It is also going into the positive direction so it is